Clarification of morphological characters and geographical distribution of Artemisia neosinensis (Asteraceae, Anthemideae), a strikingly misunderstood species from China - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2022)
Based on observations on both herbarium specimens (including type material) and living plants in the wild, we demonstrate that the Chinese species Artemisia neosinensis (Asteraceae, Anthemideae) has been strikingly misunderstood by previous authors and its geographical range has been wrongly largely extended. All the non-type specimens cited under this species by them belong to misidentifications, whereas the specimens of true A. neosinensis have been wrongly referred to other species. This species is characterized by having 1-pinnatisect, adaxially tomentose, abaxially arachnoid-tomentose leaves with ovate-acuminate or ovate lobules of segments, and campanulate capitula with abaxially arachnoid-tomentose phyllaries. It is distributed only in western Sichuan and northwestern Yunnan, not in Gansu, Qinghai and Xizang. The syntypes of A. strongylocephala var. sinensis f. virgata, a synonym of A. neosinensis, include two taxa, A. neosinensis and A. tangutica var. tomentosa. Lectotypification is thus proposed for A. strongylocephala var. sinensis f. virgata.